A brief overview of cardioprotective signaling - Jovanović, Aleksandar (Archives of Pharmacy, 2024)
Cardioprotection is defined as the intrinsic ability of cardiac tissue to withstand challenges like ischemia-reperfusion and different metabolic stresses. Initially observed through ischemic preconditioning, the scope of cardioprotection has expanded to include other inducers of cardioprotective signaling like hypoxia, temperature fluctuations, and many pharmacological agents, suggesting the existence of shared signaling pathways and protective cascades. So far, intracellular signaling factors contributing to cardioprotection include protein kinases, the reperfusion injury salvage kinase (RISK) pathway, the Survivor Activating Factor Enhancement (SAFE) pathway, hypoxia-inducible factor-1α (HIF1α), microRNAs, Connexin 43, and many others. These factors play roles in activating downstream signaling elements and protective genes, enhancing mitochondrial function, and regulating protein expression and cytosolic functions to confer cardioprotection. SUR2A, a regulatory subunit of sarcolemmal ATP-sensitive K+ (KATP) channels, autophagy and mitochondria are highlighted as crucial end-effectors, with mechanisms like regulation of the mitochondrial permeability transition pore and activation of KATP channels being pivotal for cardioprotection. Despite advances in understanding these pathways, many aspects of cardioprotection remain to be better understood. It is a particular challenge to further explore therapeutic potentials and, finally, develop clinically viable strategies for cardiac protection.